The Influence of Transactional Leadership and Work Motivation on the Performance of Agricultural Business Employees in Karanggeneng District - Lutfi Satrio Arif; Titin Titin; Abid Muhtarom (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the influence of transactional leadership and work motivation on employee performance. The research uses a quantitative approach with a survey method. The research population is all agricultural business employees in Karanggeneng District, Lamongan Regency, as many as 346 employees. The sample was determined using the Slovin formula and simple random sampling technique so that 185 respondents were obtained. Data was collected through interviews and questionnaires, then analyzed using IBM SPSS through validity tests, reliability tests, classical assumption tests, multiple linear regression, t tests, F tests, and determination coefficients. The results showed that transactional leadership had a positive and significant effect on employee performance (t = 7.130; sig. = 0.000). Work motivation also has a positive and significant effect on employee performance (t = 3.055; sig. = 0.003). Simultaneously, transactional leadership and work motivation had a significant effect on employee performance (F = 30.377; sig. = 0.000). The R-Square value of 0.524 indicates that 52.4% of employee performance variations can be explained by transactional leadership and work motivation, while the rest are explained by factors outside the model. Based on standardized beta values, transactional leadership is the most dominant variable in influencing employee performance.